Assisted reproductive technology treatment in women with severe eating disorders: a national cohort study. (7th September 2015) - Assens, Maria; Ebdrup, Ninna H.; Pinborg, Anja; Schmidt, Lone; Hougaard, Charlotte O.; Hageman, Ida
Abstract Introduction This national retrospective cohort study investigates the prevalence of women with severe eating disorders in assisted reproductive technology (ART) treatment compared with an age‐matched background population without ART treatment. It assesses the frequency distribution of the first and last eating disorder diagnosis before, during, and after ART treatment, and evaluates differences in obstetric outcomes between women with and without a severe eating disorder. Material and methods Hospital‐diagnosed eating disorders among 42 915 women in the Danish National ART cohort (DANAC), registered during 1994–2009 in the mandatory Psychiatric Central Research Register, were compared with a non‐eating disorder ART cohort of 42 644 women and an age‐matched background population of 215 290 women without a history of ART treatment for the main outcome measures prevalence of eating disorders, frequency distribution of diagnoses before/during/after ART treatment, as well as ART treatment and obstetric outcomes. Results In the ART cohort, 271 women (0.63%) had an eating disorder diagnosis compared with 0.73% in the background population (p = 0.025). The prevalence of ovulatory disorder was significantly higher in women with a severe eating disorder compared with the ART cohort without eating disorders. Obstetric outcomes were similar in ART‐treated women with and without an eating disorder. Conclusion Women with severe eating disorders were identified in the ART cohort, although significantly less often than in the age‐matched background population. Women with severe eating disorders suffered more often from anovulatory infertility than the ART comparison cohort without this disease. Obstetric outcomes appeared reassuring in the ART cohort with eating disorders.